2019
DOI: 10.3390/su11072108
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Investment: Interrelated among Corporate Governance, Economic Performance and Market Risks Using Investor Preference Approach

Abstract: Prior studies are lacking on the drivers of sustainable investment. Hence, this study examines the relationship between the social aspects, environmental aspects, economic benefits, market conditions, and corporate governance issues on sustainable investment. Sustainable investment has been rising since the last decade. However, sustainable investment is preceded by ethical investment, green investment, and socially responsible investment. In order to understand the sustainability of an investment before decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 37 publications
2
48
0
4
Order By: Relevance
“…Ming-Lang Tseng et al in the research used a very interesting way to analyze sustainable investments using the fuzzy set theory. The results of the study showed that corporate governance, economic performance and market risk were the causal aspects of sustainable investments [52]. Nomeda Dobrovolskiene and Rima Tamosiuniene in their article presented a sustainability-oriented model of financial resource allocation in a project portfolio and paid a lot attention to multi-criteria decision-making methods [53].…”
Section: Data and Research Methodologiesmentioning
confidence: 99%
“…Ming-Lang Tseng et al in the research used a very interesting way to analyze sustainable investments using the fuzzy set theory. The results of the study showed that corporate governance, economic performance and market risk were the causal aspects of sustainable investments [52]. Nomeda Dobrovolskiene and Rima Tamosiuniene in their article presented a sustainability-oriented model of financial resource allocation in a project portfolio and paid a lot attention to multi-criteria decision-making methods [53].…”
Section: Data and Research Methodologiesmentioning
confidence: 99%
“…Moreover, competent investment, on the one hand, positively affects the sustainable development of the enterprise, and on the other hand, directly depends on the current stability of the company (M.L. Tseng et al 2019) [21]. This two-sided dependence necessitates the development of methodological approaches to the management of investment activities of industrial enterprises in the context of increasing the sustainability of their development.…”
Section: Methodology and Description Of The Techniquementioning
confidence: 99%
“…For example, focusing on SDGs and exchanged-traded funds (ETF), Miralles-Quirós et al [7] concluded that investing in this type of product, which tracks companies linked to SDGs, is appropriate for two different reasons: (i) it leads to a better world while providing a financial return, and (ii) better performance improvements are obtained, as investment in companies that strive for economic growth (SDG 8) and the expansion of industry, innovation, and infrastructure (SDG 9) provide better results in performance and cumulative returns. Other studies have also concluded that sustainable investment offers high-excess returns, high market values, and shareholder loyalty [32]. In sum, previous literature has considered SRI from an SDG perspective, but there is space to have a deeper understanding of SDGs under the lens of SIBs, given that social bonds link responsible investment and social partnerships and, therefore, SDGs.…”
Section: New Forms Of Investment In the Context Of Sdgsmentioning
confidence: 99%